Marvels of illusion: illusion and perception in the art of Salvador Dali - Martinez-Conde, Susana; Conley, Dave; Hine, Hank; Kropf, Joan; Tush, Peter; Ayala, Andrea; Macknik, Stephen L. (Frontiers in Human Neuroscience, 2015)
The surrealist movement aimed to blur the distinction between the real and the imagined. Such lack of a border between demonstrable truth and fantasy is perhaps most apparent in the art of Spanish painter Salvador Dali (1904-1989). Dali included numerous illusions in his artworks, with the intent to challenge the viewers’ perceptions of reality and to enable them to see beyond the surface. The “Marvels of Illusion” exhibit, shown at The Dali Museum in St. Petersburg, FL., from June 14 to October 12, 2014, showcased Dali paintings, prints and sculptures centered on illusory themes. Here we review the significance of illusions in Dali’s art, focusing on the pieces displayed at the “Marvels of Illusion” exhibit.